Sekolah Minggu sebagai Solusi untuk Mengantisipasi Stagnasi dalam Pendidikan Kristen di Gereja - Liyus Waruwu (Harati: Jurnal Pendidikan Kristen, 2024)
The purpose of this research is to demonstrate the non-linear development of Christianity in relation to population growth. Christianity has been present for about 20 centuries and has proven to endure in various situations. This endurance is evidence that this religion exists according to God's will as the creator of the world, aimed at guiding humanity to align with the divine plan. However, it is unfortunate that the graph of Christianity in terms of quality and quantity shows a tendency to remain constant. The research conducted is an ethnographic study that employs qualitative methods with triangulation techniques to gather data, analyzed using ethnomethodology. The results indicate a 60% decline in quality over four years from 2019 to 2022, and quantity does not align with population growth, sourced from data of five selected denominations around Medan, North Sumatra, Indonesia. This research illustrates the realities and hopes related to the importance of Sunday school organized by the church to maintain existence in terms of quality and quantity among Christians today.